Habitat analysis of the commercial tuna of the Eastern Tropical Pacific Ocean. (11th April 2018) - Hu, Chen; Harrison, Daniel P.; Hinton, Michael G.; Siegrist, Zachary C.; Kiefer, Dale A.
Abstract: We have extracted information on the habitats of bigeye ( Thunnus obesus ), skipjack ( Katsuwonus pelamis ) and yellowfin ( Thunnus albacares ) in the Eastern Tropical Pacific Ocean by matching the spatial‐temporal distribution of catch and effort of purse seine and longline fleets collected by the Inter‐American Tropical Tuna Commission with oceanographic conditions and subjecting the matched data to Quotient Analysis and General Additive Models (GAMs). These analyses yielded the following results. The habitats defined by the GAM analysis of young fish differ significantly between two periods, one before and one after the introduction of fish aggregation devices (FADs). This was not true for the older fish caught by longline. We speculate that these changes were caused by the extensive use of FADs. Younger bigeye and yellowfin caught by the purse seine fleet have a different preference of environmental variables compared to older fish caught by longline. This is to be expected since tuna of different age groups have different sizes, metabolic capabilities and swimming skills. Moreover, as revealed by GAMs, the habitats of young fish differ between species to a much larger degree than those of older fish. Our results indicate the fundamental differences between fishing methods, targeted species, and operating region of the two fisheries. Specifically, young bigeye occupy equatorial waters farther from the coast and where the hypoxic layer is deeper, young skipjack occupy more productive waters associated with equatorial and coastal upwelling, and young yellowfin occupy broad areas where waters are underlain by a shallow hypoxic layer.